Why Did Public Banks Lend More During the Global Financial Crisis? - Bosshardt, Joshua (IMF Working Papers; Working Paper ;, 2020)
During the Global Financial Crisis (GFC), state-owned or public banks lent relatively more than domestic private banks in many countries. However, data limitations have hindered a thorough assessment of what led public banks to better maintain lending during the GFC. Using a novel bank-level dataset covering 25 emerging market economies, we show that public banks lent relatively more during the GFC because they pursued an objective of helping to stabilize the economy, rather than because they had superior fundamentals or access to public or depositors' funding. Nonetheless, their countercyclical behavior seems unique to the GFC rather than a regular characteristic of public banks before and after the GFC.